Outcomes of Barlow mitral valve repaired by robot-assisted keyhole surgeryCentral MessagePerspective - Ryuta Seguchi, MD, PhD; Go Watanabe, MD, PhD; Norihiko Ishikawa, MD, PhD; Yuki Kato, MD; Motomu Miyagi, MD; Toru Koakutsu, MD; Takafumi Horikawa, MD; Naoki Miyayama, MD; Sayaka Shigematsu, MD; Kazuto Miyata, MD, PhD; Shigeyuki Tomita, MD, PhD; Toshiya Ohtsuka, MD, PhD (JTCVS Techniques)
Objective: To present our strategy and the clinical outcomes of robot-assisted Barlow mitral valve keyhole surgery. Methods: From May 2015 to March 2022, a total of 1281 patients underwent mitral valve repair at our institution, including 763 with robotics surgeries. Of these, 124 patients with Barlow mitral valve (49 ± 12 years, male/female ratio = 81:43) were treated using robotic assistance and included in this study. Results: All operations were completed using 3 to 5 keyholes. Neochordae implantation using the loop technique was the first option, and resection was performed only in cases with an intrinsic risk of developing systolic anterior motion. Neochordae implantation was performed in 118 cases (95.1%) using 6.6 ± 3.0 neochordae. Posterior leaflet resection was performed in 27 (21.7%) patients. Operation time was 177 ± 42 minutes, cardiopulmonary bypass time was 127 ± 25 minutes, and aorta crossclamp time was 76 ± 16 minutes. Blood transfusion was required in 5 cases (4%). None of the patients required a conversion to valve replacement. The postoperative complications included bleeding (n = 4), stroke (n = 1), and infection (n = 2). Mitral valve regurgitation 1 week after repair was none or trivial in 122 cases (98.3%), mild in 2 cases (1.7%), and more than moderate in 0 cases. Freedom from reoperation was 99.2% during the follow-up period of 36 ± 21 months. One patient required reoperation due to infective endocarditis. Conclusions: Robot-assisted keyhole surgery using the loop-first concept was adequate to help achieve satisfactory and safe perioperative outcomes for Barlow mitral valve.